Labor issues in infrastructure reform : a toolkit - World Bank; World Bank.; Public-Private Infrastructure Advisory Facility (Washington, DC : World Bank, 2003)
The toolkit provides practical tools and information to help policy makers and practitioners deal with the sensitive issues involved with infrastructure reform in the public services. It is illustrated with examples, checklists, and templates that walk decision makers through best practice methodologies.
Includes bibliographical references.
oif 30/06/14, ijb, 31/01/2019
Loan
Keywords: Public contracts; Public works - employees; Public works - cost effectiveness; Infrastructure (Economics); Labor contract; Contracting out; Public works - personnel management; Public works - management